Pendampingan Program Inovasi BUMDes Berbasis Potensi Desa oleh Mahasiswa KKN UM Palembang - Sunardi Sunardi; Al-Afghani Gumay Putra; Ahmad Syakirin; Asniar Merly Arlita; Linka Meyitin; Nadhirah Khalisha Putri; Tanzila Rosita; Bagus Prasetiono; Feri Erlangga; Muhammad Azka Abdullah; Aldi Ansah (PELITA NUSA TENGGARA, 2026)
Village-Owned Enterprises are strategic instruments in promoting inclusive and sustainable rural economic development, in line with the achievement of the Village Sustainable Development Goals (Village SDGs), particularly the goals of no poverty, decent work and economic growth, and partnerships for development. However, BUMDes Kompak S in Sungai Pinang Nibung Village, Sungai Pinang Sub-district, Ogan Ilir Regency faces several challenges, particularly in terms of institutional governance, business innovation, and product marketing. This community service activity aims to strengthen institutional capacity and enhance business innovation through student-based Community Service Program assistance as an implementation of the Higher Education Key Performance Indicators (IKU), especially off-campus learning and tangible contributions to society. The activity employed a participatory and collaborative approach, including situational analysis, program planning, management and business innovation assistance, strengthening digital marketing, and activity evaluation. The results indicate improvements in BUMDes governance, the development of standard operating procedures (SOPs), increased product innovation based on local potential, and expanded marketing reach through digital platforms. These outcomes contribute to strengthening the rural economy, enhancing community self-reliance, and supporting the national development agenda (Asta Cita) through the reinforcement of people-centered economic development and villages as centers of growth. Overall, this program effectively addressed partner challenges and supported sustainable village development.